Environmental views and behaviors of municipality employees and confounding factors - (:unkn) unknown (My University, 2011)
Environmental environment is defined as "a human notices significance of his/her relation with the environment in terms of his/her existence". In the society, several professional groups are of extreme importance for increasing awareness of subjects and leading to behavior changes. Environmental behaviors of physicians having substantial effects on public health and education are important for social awareness. This study is conducted in order to assess environmental behaviors of municipality employess and confounding factors. © SGEM2011 All Rights Reserved by the International Multidisciplinary Scientific GeoConference SGEM.
Keywords: Environmental behavior; Environmental view; Municipality employees